Building an Improved Drought Climatology Using Updated Drought Tools: A New Mexico Food-Energy-Water (FEW) Systems Focus - Johnson, Lindsay E.; Geli, Hatim M. E.; Hayes, Michael J.; Smith, Kelly Helm (Frontiers in Climate, 2020)
Drought is a familiar climatic phenomenon in the United States Southwest, with complex human-environment interactions that extend beyond just the physical drought events. Due to continued climate variability and change, droughts are expected to become more frequent and/or severe in the future. Decision-makers are charged with mitigating and adapting to these more extreme conditions and to do that they need to understand the specific impacts drought has on regional and local scales, and how these impacts compare to historical conditions. Tremendous progress in drought monitoring strategies has occurred over the past several decades, with more tools providing greater spatial and temporal resolutions for a variety of variables, including drought impacts. Many of these updated tools can be used to develop improved drought climatologies for decision-makers to use in their drought risk management actions. In support of a Food-Energy-Water (FEW) systems study for New Mexico, this article explores the use of updated drought monitoring tools to analyze data and develop a more holistic drought climatology applicable for New Mexico. Based upon the drought climatology, droughts appear to be occurring with greater frequency and magnitude over the last two decades. This improved drought climatology information, using New Mexico as the example, increases the understanding of the effects of drought on the FEW systems, allowing for better management of current and future drought events and associated impacts.